Adoption of AI in Firms and the Issues to be Overcome - An Empirical Analyses of the Evolutionary Path of Development by Firms - Kumiko Miyazaki; Sato; Ryusuke (International Telecommunications Society (ITS), 2018)
AI has been through several booms and we have currently reached the 3rd AI boom. Although AI has been evolving over six decades it seems that the current boom is different from the previous booms. In this paper, we attempt to elucidate the issues for widespread adoption of AI in firms. Through one of the authors work experience related to AI, it appears that although companies are willing to consider adopting AI for various applications, only a few are willing to make a commitment to go for full scale adoption. The main goal of this paper is to identify the characteristics of the current 3rd AI boom and to analyze the issues for adoption by firms. For this purpose we have put forward 3 research questions. 1) How has the technological performance in AI changed at the national level during the 2nd and the 3rd boom? 2) How have the key technologies and the applications of AI changed over time? 3) How is the companies' perspective on AI and what are the necessary conditions for firms to adopt AI? Through bibliometric analysis, we were able to extract the important keywords in the 3rd AI boom, which were Machine learning and Deep learning. The main focus of AI research has been shifting towards AI applications. The interviews with firms which were considering adopting AI suggested the existence of a gap between the needs of the company and what AI can deliver at present. AI could be used for finding suitable treatment for genetic illnesses if some issues are solved.
Keywords: 330